"Infortunios de Alonso Ramírez": una autobiografía en colaboración - Ortiz Gambetta, María Eugenia (2013)
Carlos Siguenza's Infortunios de Alonso Ramírez is one of the most widely known colonial chronicles. It is a "relación" a first-person legal document, though in this case, the author does not identify with the narrator. This gave rise to a question of genre that was one of the most debated questions that the novel?s critics engaged with. Given this diversity of approaches to this text, I propose considering it as a "collaborative autobiography" following Philippe Lejeune, a model that gives us a perspective from which the novel can be considered as a result of intertwined embodied voices.